Mask-free regrowth of GaN p-i-n structure on selective-area Si-implanted n-GaN template layer. (15th April 2016) - Sheu, Jinn-Kong; Chen, Po-Cheng; Yeh, Yu-Hsiang; Kuo, Shih-Hsun; Lee, Ming-Lun; Liao, Po-Hsun; Lai, Wei-Chih
Abstract: GaN p-i-n homoepitaxial structures are in-situ formed through mask-free selective-area growth (SAG) on Si-implanted GaN (SIG) templates. Selective-area Si implantation on GaN layer creates damaged surface regions that lead to lattice distortion from the neighboring implantation-free regions. GaN homoepitaxial regrowth occurs preferentially on the implantation-free regions when the SIG films serve as growth templates. The optical and electrical characteristics of the GaN p-i-n diodes formed by mask-free SAG are comparable to those of diodes fabricated by conventional technique. The GaN p-i-n photodiodes exhibit typical ultraviolet (UV)-to-visible (360/480 nm) spectral rejection ratios over three orders of magnitude. With forward injection currents of 10–100 mA, the proposed GaN diodes exhibit a UV emission at around 362 nm because of the band–edge transition between shallow donor states and the valence-band edge, rather than defect-related emission. Graphical abstract: